Experience of chinese counter-marching nurses with COVID-19 patients' death in Wuhan: a qualitative study - Zhifang Guo; Kunli Wu; Huibin Shan; Younglee kim; Qilian He (BMC, 2023)
Abstract Background The COVID-19 pandemic was occurring worldwide with over a 6.5 million deaths. It's important to explore the instructions for the global nursing community by identifying the personal coping methods of Chinese nurses in Wuhan to deal with patient deaths. Methodology The study used a qualitative conventional content analysis with 14 Chinese Counter-marching nurses. Purposive sampling, snowball sampling, and semi-structured interviews were used for participants and data collection. To assess the quality of the findings, Guba and Lincoln's criteria for confidence were fulfilled. Results The data analysis results in 4 main categories:(1) psychological shocks related to COVID-19 patient's death; (2) personal psychological adjustment and demands; (3) insights on life and values; (4) Needs for relevant knowledge and skills. Conclusions During the outbreak of the epidemic or pandemic, adequate psychological care resources need to be provided to nurses when facing the death of infectious patients, to reduce the negative emotions brought by death. Effective coping strategies should also be formulated to enhance their resilience and promote their professional competence.